Synthesis of Novel Hybrids of Thymoquinone and Artemisinin with High Activity and Selectivity Against Colon Cancer - Fröhlich, Tony; Ndreshkjana, Benardina; Muenzner, Julienne K.; Reiter, Christoph; Hofmeister, Elisabeth; Mederer, Sandra; Fatfat, Maamoun; El Baba, Chirine; Gali-Muhtasib, Hala; Schneider-Stock, Regine; Tsogoeva, Svetlana (ChemMedChem, 2017)
Colorectal cancer causes 0.5 million deaths each year. To combat this type of cancer the development of new specific drug candidates is urgently needed. In the present work seven novel thymoquinone-artemisinin hybrids with different linkers were synthesized and tested for their in vitro anticancer activity against a panel of various tumor cell lines. The thymoquinone-artesunic acid hybrid 7 a, in which both subunits are connected via an ester bond, was found to be the most active compound and selectively decreased the viability of colorectal cancer cells with an IC50 value of 2.4 ?m (HCT116) and 2.8 ?m (HT29). Remarkably, hybrid 7 a was up to 20-fold more active than its parent compounds (thymoquinone and artesunic acid), while not affecting nonmalignant colon epithelial HCEC cells (IC50 >100 ?m). Moreover, the activity of hybrid 7 a was superior to that of various 1:1 mixtures of thymoquinone and artesunic acid. Furthermore, hybrid 7 a was even more potent against both colon cancer cell lines than the clinically used drug 5-fluorouracil. These results are another excellent proof of the hybridization concept and confirm that the type and length of the linker play a crucial role for the biological activity of a hybrid drug. Besides an increase in reactive oxygen species (ROS), elevated levels of the DNA-damage marker ?-H2AX were observed. Both effects seem to be involved in the molecular mechanism of action for hybrid 7 a in colorectal cancer cells.
EVALuna2:6899